A qualitative exploration of the prescribing and use of statins in asymptomatic people in Ireland: A case of medicalisation, biomedicalisation and pharmaceuticalisation. (September 2021) - Byrne, Paula; O'Donovan, Órla; Smith, Susan M; Cullinan, John
There has been a notable increase in the use of statins in people without cardiovascular disease but who may be at risk in the future. The majority of statin users now fall into this category but little research has focused exclusively on this group. Debate has ensued regarding medicating asymptomatic people, and processes described variously as medicalisation, biomedicalisation and pharmaceuticalisation are used to explain how this happens. These overlapping and interrelated processes require issues to be 'problemised' as medical problems requiring medical solutions given the prevailing understandings of health, risk and disease. However, current understandings of risk and disease are not simply the result of technological and scientific advances, they are also socially constructed. We interviewed members of the public, GPs and others, and found that rather than high cholesterol being seen as one of several risk factors that contributes to heart disease, it tended to be promoted simplistically to the status of a disease needing treatment of itself. Statins were justified by those taking them as different to 'unnecessary medicines'. However, some participants demonstrated resistance to statins, worried about over-medicalisation and deviated from accepted practices, indicating a complex 'muddling through' in the face of uncertainty.